2008
DOI: 10.2214/ajr.07.2635
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body MRI Versus Whole-Body MDCT for Staging of Multiple Myeloma

Abstract: Whole-body MDCT leads to a significantly lower detection rate and staging in patients with multiple myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
115
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(122 citation statements)
references
References 20 publications
0
115
1
6
Order By: Relevance
“…More recently, MRI was included in staging procedures because of its exceptional sensitivity in the detection of tumour spread, especially in the spine [11][12][13][14]. However, MRI is also insensitive for the interim assessment of therapy response [15]. The use of PET in MM started relatively late in comparison to PET in lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, MRI was included in staging procedures because of its exceptional sensitivity in the detection of tumour spread, especially in the spine [11][12][13][14]. However, MRI is also insensitive for the interim assessment of therapy response [15]. The use of PET in MM started relatively late in comparison to PET in lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Baur-Melnyk et al 60 found that MRI revealed more extensive disease in half of the patients evaluated when compared with whole-body CT. MRI detected focal plasmacytomas within the marrow before the development of osteolytic changes that were visible by CT or X-ray. [60][61][62] Bannas et al 63 prospectively evaluated 31 patients following ASCT with imaging techniques compared with standard laboratory response criteria. PET/CT had a sensitivity of 50% and a specificity of 85%, and MRI had a sensitivity of 80% and a specificity of 38%.…”
Section: Imagingmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is increasingly used in the diagnosis of multiple myeloma, and the recent consensus statement of the International Myeloma Working Group (IMWG) introduced the role of Whole-body Magnetic resonance imaging (WB-MRI) in the management of patients with this haematological disease (3). WB-MRI is recommended in the initial staging of patients with MM due to its high sensitivity in detecting focal lesions or diffuse infiltration of bone marrow, soft tissue injuries, extraosseous lesions as well as for the assessment of treatment response (4).…”
Section: Introduction Introductionmentioning
confidence: 99%